WHITELEG SHRIMP (Litopenaeus vannamei Boon, 1931) IN A SELECTED SHRIMP FARM OF SOUTH GUJARAT (INDIA) (Applied Biological Research, 2023)
Whiteleg shrimp (Litopenaeus vannamei Boone, 1931) being specific  pathogen-free and specific pathogen-resistant fast growing less aggressive  species is becoming the choice of farmers for culture. The length-weight  relationship helps to explain the stocks; and comparative growth studies  are recorded for culture management purposes. In present study, 1200  individuals of Pacific shrimp (L. vannamei) were investigated for length weight relationship (LWR) and condition factor (K). The specimens were  randomly collected during January to March 2020 from Dhanlaxmi Aqua  Farm, Palsana, Valsad district, Gujarat (India). The length-frequency  distribution showed that length group 12.00-14.00 cm was dominant with  447 specimens followed by 14.00-16.00 cm (445), 10.00-12.00 cm (183),  14.00-16.00 cm (101), 8.00-10.00 cm (21) and 18.00-20.00 cm (3). The  correlation coefficient (r2) 0.854, intercept (a) -1.994, regression coefficient  (b) 2.897 and regression coefficient or growth constant (b) 2.897 (< 3.000)  indicated negative allometric growth of white leg shrimp. The values of K  obtained were ≤ 1.0 and suggested good and normal growth of shrimp  indicating the better adoption of farmmanagement practices during the  culture period. These findings may be useful for shrimfarm managers to  have better operational activities and assess the health and habitat conditions of rearing shrimps.
Keywords: Condition factor; growth; length-weight relation; Pacific shrimp